Seeking commonalities or avoiding differences? Re-conceptualizing distance and its effects on internationalization decisions - Williams, David W; Grégoire, Denis A (Journal of International Business Studies, 2015)
Past research established distance’s key influence on internationalization. However, theoretical issues, methodological challenges, and inconsistent results hinder scholarship on why distance plays such an influential role. To address these problems, we draw from cognitive research on similarity comparisons to re-conceptualize distance and test a model of internationalization decisions. Analyzing the verbal protocols of executives considering a series of internationalization opportunities, we demonstrate that, over and above objective distance indicators, considerations that reduce distance (commonalities) and considerations that augment distance (differences) have distinct effects on decisions of where, when, and how to internationalize. As such, our study contributes new insights for understanding the nature and effects of distance, across different dimensions of distance and internationalization decisions. Moreover, internationalization theories have come to emphasize different theoretical rationales for explaining the influential role of distance on different decisions. By integrating these rationales together with the notion that distance-reducing commonalities and distance-augmenting differences have distinct implications for internationalization decisions, we introduce the notion that it is not only the addition of distance considerations that matters but also the directionality of such changes. Doing so, our study points to new theoretical and methodological insights to help address prior criticisms and advance future research.